2015
DOI: 10.1007/s13193-015-0434-8
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma of Rectum: How to Treat?

Abstract: Squamous cell carcinoma (SCC) of rectum is an uncommonly seen malignancy. It has been difficult to establish the precise etio-pathogenesis due to paucity of cases. For the same reason, the rigorous treatment protocol has not been defined. The available compendium of knowledge about this pathology is based on isolated case reports and case series. We report a case of SCC of rectum who was treated with chemo-radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…So far, while different theories have been proposed, the etiology of rectal SCC is still debated ( 1 , 2 ). It has been suggested that rectal SCC could originate from pluripotent stem cells that could differentiate into different lineages ( 6 ). Other groups suggested a potential malignant evolution from persistent ectopic embryonal nests of ectodermal cells ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…So far, while different theories have been proposed, the etiology of rectal SCC is still debated ( 1 , 2 ). It has been suggested that rectal SCC could originate from pluripotent stem cells that could differentiate into different lineages ( 6 ). Other groups suggested a potential malignant evolution from persistent ectopic embryonal nests of ectodermal cells ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, several associations have been observed. Some cases reports have been found SCC in association with inflammatory bowel diseases involving colon and rectum, ulcerative colitis (8) , infections including Schisotomiasis and Entamoeba Histolitica (8) , previous radiation exposure to the pelvis (9) and immunosuppressive state (10) . Although a clear association betwen SCC of anal canal and Human Papilloma Virus (HPV) exists, similar relation with rectal SCC has not been etablished.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy should target the tumour, mesorectum, presacral nodes and internal iliac nodal basins. 39 Similar to aSCC treatment guidelines, most case reports and series of rSCC have used 5-FU associated with MMC or cisplatin 44 , 45 , 46 , 47 as the CRT regimen ( Table 3 ) with encouraging outcomes (most patients alive with no evidence of disease in a long follow-up).…”
Section: Treatment Optionsmentioning
confidence: 99%